Related male Drosophila melanogaster reared together as larvae fight less and sire longer lived daughters. Issue 14 (24th June 2015) - Carazo, Pau; Perry, Jennifer C.; Johnson, Fern; Pizzari, Tommaso; Wigby, Stuart
Abstract Competition over access to reproductive opportunities can lead males to harm females. However, recent work has shown that, in Drosophila melanogaster, male competition and male harm of females are both reduced under conditions simulating male‐specific population viscosity (i.e., in groups where males are related and reared with each other as larvae). Here, we seek to replicate these findings and investigate whether male population viscosity can have repercussions for the fitness of offspring in the next generation. We show that groups of unrelated‐unfamiliar (i.e., unrelated individuals raised apart) males fight more intensely than groups of related‐familiar males (i.e., full siblings raised together as larvae), supporting previous findings, and that exposure to a female is required to trigger these differential patterns of male–male competition. Importantly, we show that differences in male–male competition can be associated with transgenerational effects: the daughters of females exposed to unrelated‐unfamiliar males suffered higher mortality than the daughters of females exposed to related‐familiar males. Collectively, these results suggest that population structure (i.e., variation in the relatedness and/or larval familiarity of local male groups) can modulate male–male competition with important transgenerational consequences.